Culture Based Learning to Respond Lineslide Disaster - Ucu Rahayu; Mestika Sekarwinahyu (Bandar Lampung University (UBL), 2013)
Landslides are natural disasters that often occurs in Indonesia. The main triggers landslide is rainwater and human behavior that are not wise to the environment. On the other hand, recently a lot of high school students who are less familiar with local culture. Efforts recognition and preservation of culture needs to be encouraged back in schools. Therefore, this paper will elaborate on West Java culture-based learning in the context of landslide mitigation for elementary school students. Culture of West Java which is integrated into the learning avalanche response is in the form of traditional games, and children's songs (stanzas) of West Java. This paper is part of a national strategic research titled Development Package Learning for Elementary Students in disaster prone regions. The results showed that there was an increase in learning outcomes obtained by elementary school students, and learning becomes more interesting and fun for them.